The Steger Homestead kitchen : simple recipes for an abundant life - Steger, Will; Steger, Rita Mae; Dooley, Beth (Minneapolis : University of Minnesota Press, 2021)
"Personal and simple, earthy and warm-recipes and stories from the Steger Wilderness Center in Minnesota's north woods"--.
Includes index.
Keywords: Cooking, American -- Minnesota; Cooking -- Minnesota; Cooking, American -- Midwestern style; simple recipes; homestead cooking; Cookbooks